Pengaruh Penggunaan Media Statis-Dinamis pada Sistem Reproduksi Manusia terhadap Penguasaan Konsep Siswa - Khoiroh, Miya Nisaul; santosa, Slamet; ramli, Murni (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
This study aims to examine teh effect of static, dynamic, and static dynamic media to conceptual understanding of students grade XI. The participant were selected using a cluster sampling and selected samples were class scince 3, science 5, science 6, and science 7. Science 7 as control class, Science 3 as first experiment class that use static media, Science 5 as second experiment class(dynamic media), and science 6 as third experiment class with static-dynamic media. The total participants were 148 students. Learning was focused on the topic of human reproductive system. The conceptual understanding of students was assesed by two-tier test at the end of experiment. Data was analyzed analyzed by One Way ANOVA test with Î± = 0.05,Â  and further tested with Duncan test. The results are (1) there is an effect of type of media used to the conceptual understanding of students; (2) static-dynamic media shows the highest score. It is concluded that static-dynamic media can be recommended to apply in the biology class, particularly on human reproductive system